Energy analysis for lighting system in academic building - case study in IKM Bintulu - Akin, Aisyah Gwynnie Chembat (2016)
The main purpose of this project is to conduct an energy audit in academic buildings which are directly focused on the lighting system. To analyze and identify the energy consumption and efficiency of the academic building in IKM Bintulu is the main study throughout this project. 15% to 25% of the energy consumed at campus is from the usage of lighting and any energy efficiency measures in this area will provide very good opportunities especially in the economic branch. One of the two main reasons of more energy consumed from the common thought that it is more economical to leave fluorescent lighting on than to turn on and off as required. The second is that in the past lighting systems which uses older less efficient lamps and fittings, and due to the low costs of energy, over-lighting was common practice. Data collection will include lighting intensity measurement and energy calculation comparison. The outcome of the analysis will provide the input for energy efficient measures proposal.